Impact of intratumoural heterogeneity on the assessment of Ki67 expression in breast cancer - Aleskandarany, Mohammed A.; Green, Andrew R.; Ashankyty, I.; Elmouna, A.; Diez-Rodriguez, Maria; Nolan, Christopher C.; Ellis, Ian O.; Rakha, Emad (Springer, 2016)
In breast cancer (BC), the prognostic value of Ki67 expression is well-documented. Intratumoural heterogeneity (ITH) of Ki67 expression is amongst the several technical issues behind the lag of its inclusion into BC prognostic work-up. The immunohistochemical (IHC) expression of anti-Ki67 antibody (MIB1 clone) was assessed in four full-face (FF) sections from different primary tumour blocks and their matched axillary nodal (LN) metastases in a series of 55 BC. Assessment was made using the highest expression hot spots (HS), lowest expression (LS), and overall/average expression scores (AS) in each section. Heterogeneity score (Hes), co-efficient of variation, and correlation co-efficient were used to assess the levels of Ki67 ITH. Ki67 HS, LS, and AS scores were highly variable within the same section and between different sections of the primary tumour, with maximal variation observed in the LS (P\0.001). The least variability between the different slides was observed with HS scoring. Although the associations between Ki67 and clinicopathological and molecular variables were similar when using HS or AS, the best correlation between AS and HS was observed in tumours with high Ki67 expression only. Ki67 expression in LN deposits was less heterogeneous than in the primary tumours and was perfectly correlated with the HS Ki67 expression in the primary tumour sections (r = 0.98, P\0.001). In conclusion, assessment of Ki67 expression using HS scoring method on a full-face BC tissue section can represent the primary tumour growth fraction that is likely to metastasise. The association between Ki67 expression pattern in the LN metastasis and the HS in the primary tumour may reflect the temporal heterogeneity through clonal expansion.